THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF RESEARCHING CRISES IN PUBLIC ADMINISTRATION - Sokolov, Alexander (Public Administration and Regional Development, 2021)
The purpose of the article is to determine the theoretical and methodological foundations of the study of crises in public administration. The methodological basis of the study are general theoretical methods (analysis and synthesis), as well as the principles of historicism, objectivity and science. The scientific novelty lies in the unique author's definition and analysis of crises in public administration. Conclusions. It has been studied that a crisis in the general sense is an unstable or critical period that inevitably leads to change and contains a high probability of extremely undesirable consequences. In turn, the "crisis of public administration" is a special form of system of public authorities and civil society, accompanied by instability, reduced control over socio-economic processes, imbalance of political institutions, exacerbation of social conflicts, growing contradictions in society and more. Such a crisis leads to a decrease in the effectiveness and efficiency of managerial influence on socio-economic processes. The crisis is considered as a complex phenomenon covering a wide range of events. These events may differ in scale, causes, duration, severity, etc., but they are united by the fact that they threaten the main interests and reputation of the organization, government or state, require immediate response and the use of non-traditional means of settlement, significantly change the situation, normal course. society and relations between the parties to the conflict. It is analyzed that public administration crises can be both mild and deep, both short-term and prolonged, both local and continuous, both hidden and overt, both acute and chronic. It was found that in case of ignoring or untimely response to crises, they can not only cause material damage, but also negatively affect the goals of the organization and the state.